Gambaran Risiko Gangguan Jiwa pada Korban Bencana Alam Gempa di Lombok Nusa Tenggara Barat - Meidiana Dwidiyanti; Irwan Hadi; Reza Indra Wiguna; Hasanah Eka Wahyu Ningsih (Holistic Nursing and Health Science, 2018)
Background: Earthquake is known as a disaster causing considerable health problems requiring immediate post trauma rehabilitation. Prominent health problem emerging after a disaster is psychiatric and mental health problem.Purpose: The study aimed to identify mental health risk and other significant problems growing among the victim’s post-earthquake in Lombok, West Nusa Tenggara, Indonesia.Method: Mix method approach, which was used throughout the study, is a strategy to obtain the data from the disaster victims of 88 people in Lombok. This study collected the data using Psychiatric and Mental Health Disorder Detection Questionnaire and symptom documentation form after practicing Mindfulness Spiritual.  Results:  The result showed that victims experienced neurosis symptom (85,2%), psychotic symptom (25,9%), PTSD symptom (64,7%) and 13 people did not experience mental health disorder risk. The qualitative study result showed that the earthquake victims grievance was afraid and feeling anxiety to enter the house due to earthquake incident, family relationship and economy problems, ghost issue and numerous diseases.Conclusion: Earthquake lead to psychiatric and mental health disorder and problems including mental health, economy, spiritual and physic aspects among people in Lombok, West Nusa Tenggara.  It is essential for the future research to conduct a research about the description of mental health disorder after practicing mindfulness spiritual and planning the intervention that had been agreed by the respondent.